Correction: Lee, B.U. Minimum Sizes of Respiratory Particles Carrying SARS-CoV-2 and the Possibility of Aerosol Generation. Int. J. Environ. Res. Public Health 2020, 17, 6960 - Byung Uk Lee (MDPI AG, 2021)
The author would like to update a few calculation results in the Abstract and Section 4 “Calculation of Sizes of Respiratory Particles Containing SARS-CoV-2” in the previous publication [...]